GAMBARAN PENGETAHUAN MAHASISWA TINGKAT II TENTANG LAUDATO SI DI STIKES SANTA ELISABETH MEDAN TAHUN 2023 - Indra Hizkia Perangin angin; Erlita Simalango (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Knowledge is the result of knowing through sensory processes, especially the eyes and ears of objects. Knowledge is a very important domain for the formation of open behavior. Laudato Si is the care of our common home, taking care of nature's house is the original vocation of humans since humans are created. This understanding influences human life behavior in treating nature as a home. The love for nature changed the way of life for Franciscus Assisi by repenting and making peace with nature. The Encyclical Laudato Si is written by Pope Francis, the figure who inspired him is Franciscus Assisi. The research objective is to find out the level II student's knowledge about Laudato Si at STIKes Santa Elisabeth Medan 2023. The research used a qualitative method where data collection is carried out using an interview technique of 4 questions so that they are able to dig deeper about Laudato Si's knowledge. The sampling technique used purposive sampling of 5 participants. The data analysis technique used is thematic analysis. The results of the study were: Laudato Si is environmental care, awareness of love for the environment in preserving the earth or the environment both from small things such as disposing of trash in its place, Laudato si can be said to be handling various types of waste that can transmit disease, Laudato si can be seen from the way of sorting and packaging various kinds of infectious and non-infectious waste, Laudato Si is waste handling by separating waste according to its type.